Epigenome characterization at single base-pair resolution - Henikoff, Jorja G. (National Academy of Sciences, 2011)
We have combined standard micrococcal nuclease (MNase) digestion of nuclei with a modified protocol for constructing paired-end DNA sequencing libraries to map both nucleosomes and subnucleosome-sized particles at single base-pair resolution throughout the budding yeast genome. We found that partially unwrapped nucleosomes and subnucleosome-sized particles can occupy the same position within a cell population, suggesting dynamic behavior. By varying the time of MNase digestion, we have been able to observe changes that reflect differential sensitivity of particles, including the eviction of nucleosomes. To characterize DNA-binding features of transcription factors, we plotted the length of each fragment versus its position in the genome, which defined the minimal protected region of each factor. This process led to the precise mapping of protected and exposed regions at and around binding sites, and also determination of the degree to which they are flanked by phased nucleosomes and subnucleosome-sized particles. Our protocol and mapping method provide a general strategy for epigenome characterization, including nucleosome phasing and dynamics, ATP-dependent nucleosome remodelers, and transcription factors, from a single-sequenced sample.